2021
DOI: 10.3389/fpsyg.2021.702398
|View full text |Cite
|
Sign up to set email alerts
|

What Influences People’s Tradeoff Decisions Between CO2 Emissions and Travel Time? An Experiment With Anchors and Normative Messages

Abstract: One of the today’s greatest challenges is to adjust our behavior so that we can avoid a major climate disaster. To do so, we must make sacrifices for the sake of the environment. The study reported here investigates how anchors (extrinsic motivational-free information) and normative messages (extrinsic motivational information) influence people’s tradeoffs between travel time and carbon dioxide (CO2) emissions in the context of car travel and whether any interactions with environmental concern (an intrinsic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…According to the authors, these anchoring effects joined the positive effects of passengers' perceptions of the effectiveness of a proposed carbon travel tax and their perceived responsibility to prevent climate change to influence high willingness to pay for the presented bid. As a second example, Andersson et al [25] demonstrated effects of anchors and normative messages on people's willingness to travel for longer periods of time to reduce carbon dioxide (CO 2 ) emissions. The authors found that participants who were assigned to a condition with a high anchor (8 h and 30 min of travel) and a normative message on CO 2 emissions (a prompt stating a target for reducing CO 2 emissions) were willing to travel for longer compared to participants in conditions of low anchors (5 h and 30 min of travel) and no normative messages.…”
Section: Anchoring Effects: Environmental Judgments Temperature Ancho...mentioning
confidence: 99%
“…According to the authors, these anchoring effects joined the positive effects of passengers' perceptions of the effectiveness of a proposed carbon travel tax and their perceived responsibility to prevent climate change to influence high willingness to pay for the presented bid. As a second example, Andersson et al [25] demonstrated effects of anchors and normative messages on people's willingness to travel for longer periods of time to reduce carbon dioxide (CO 2 ) emissions. The authors found that participants who were assigned to a condition with a high anchor (8 h and 30 min of travel) and a normative message on CO 2 emissions (a prompt stating a target for reducing CO 2 emissions) were willing to travel for longer compared to participants in conditions of low anchors (5 h and 30 min of travel) and no normative messages.…”
Section: Anchoring Effects: Environmental Judgments Temperature Ancho...mentioning
confidence: 99%